2005
DOI: 10.1037/0735-7044.119.4.1084
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Experience Produces Long-Lasting Behavioral Modifications in the Rat.

Abstract: From 5 to 22 months of age, cognitive and emotional responses of nulliparous, primiparous, and multiparous rats were assessed using a dry land maze (DLM) and an elevated plus-maze (EPM) at 4-month intervals. Parous rats exhibited improved spatial memory in the probe and competitive versions of the DLM, and more exploration in the EPM and a novel stimulus test relative to nulliparous females. The nulliparous females, however, outperformed parous rats during the DLM visual cue test at 17 months of age. At 23 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 53 publications
5
97
1
6
Order By: Relevance
“…Dams having had at least one litter typically outperform virgins on tasks of cognitive performance (Kinsley et al 1999, Love et al 2005, Bodensteiner et al 2006, Pawluski et al 2006a, Macbeth et al 2008. Primiparous or multiparous dams are found to have a greater spinal density on hippocampal dendrites compared with nulliparous dams (Pawluski & Galea 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dams having had at least one litter typically outperform virgins on tasks of cognitive performance (Kinsley et al 1999, Love et al 2005, Bodensteiner et al 2006, Pawluski et al 2006a, Macbeth et al 2008. Primiparous or multiparous dams are found to have a greater spinal density on hippocampal dendrites compared with nulliparous dams (Pawluski & Galea 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The present study supports these findings, demonstrating a greater cognitive performance in multiparous, compared with nulliparous, dams. It cannot be ignored, however, that many studies to date have either found no cognitive and/or morphological differences between primiparous and multiparous dams, or have found differences that favor primiparous over multiparous dams (Wartella et al 2003, Love et al 2005, Pawluski & Galea 2006, Pawluski et al 2006a. One explanation may be that the beneficial effects of multiple pregnancies do not summate in a long-term manner.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Parous females also have decreased anxiety-like behavior as measured in the open field (Wartella et al, 2003) and on the elevated plus maze (Neumann, 2001;Lonstein, 2005). Furthermore, recent work indicates that multiparity continues to decrease anxiety as measured on the elevated plus maze up to 18 months after last weaning (Love et al, 2005), indicating effects on behavior throughout the female's lifespan.…”
mentioning
confidence: 92%
“…Interestingly, parous females (primiparous and multiparous) continue to outperform nulliparous females on a dryland version of the Morris water maze at 6, 12, 18 and 24 months of age (Gatewood et al, 2005), and are significantly faster than NP females to find a baited food well at 13 months of age (Love et al, 2005), long past their last reproductive experience. However, one recent study indicated that, compared to NP females, primiparous but not multiparous females have significantly better spatial memory on the radial arm maze (Pawluski et al, 2006b).…”
mentioning
confidence: 99%